Association Between Family Support and Coping Strategies of People With Covid-19: A Cross-Sectional Study - Aileen M Chilon-Huaman; Ángela Camposano-Ninahuanca; Janett V. Chávez Sosa; Salomón Huancahuire‐Vega; William De Borba (My University, 2023)
Purpose: The study aimed to determine the association between family support and coping strategies of people diagnosed with COVID-19. Methods: The study was analytical and cross-sectional. The sample consisted of 500 participants who were selected by non-probabilistic and snowball sampling and included residents of both sexes who belonged to the city of Lima, with a diagnosis of COVID-19, who lived with relatives, and who accepted to participate in the research. For data collection, the scales "family support" and "Coping and Adaptation Process-Coping Adaptation Processing Scale (CAPS)" were used. The technique used was the survey through the home visit and the questionnaire instrument. To measure the relationship of the study variables, binary logistic regression was chosen, considering coping strategies as the dependent variable and socio-demographic data and family support as independent variables. Results: Of the 500 participants, 50.4% were women, and 49.6% were men. The results revealed that most participants presented a high capacity for coping strategies and high perceived family support (97.2% and 81%, respectively). In the bivariate analysis, socio-demographic aspects and family support and their dimensions were related to high or low capacity for coping strategies. Significant differences were verified between marital status (p=0.026), having children (p=0.037), family support (p=0.000), and its dimensions with coping strategies. Finally, the multivariate analysis found that people with COVID-19 who perceived high family support were 33.74 times (95% CI: 7266-156,739) more likely to have a high capacity for coping strategies. Conclusion: Therefore, it is necessary to promote the development of parental and family support skills in the face of the health emergency caused by COVID-19.
Keywords: Snowball sampling; Coping (psychology); Bivariate analysis; Social support; Cross-sectional study; Psychology; Family support; Logistic regression; Clinical psychology; Marital status; Medicine; Social psychology; Environmental health; Population; Statistics; Pathology; Internal medicine; Mathematics; Physical therapy; Snowball sampling; Coping (psychology); Bivariate analysis; Social support; Cross-sectional study; Psychology; Family support; Logistic regression; Clinical psychology; Marital status; Medicine; Social psychology; Environmental health; Population; Health Sciences Health Professions Radiological and Ultrasound Technology Family and Patient Care in Intensive Care Units; Social Sciences Psychology Clinical Psychology COVID-19 and Mental Health; Health Sciences Health Professions Pharmacy Nursing care and research